Impact of preoperative radiotherapy on patient-reported outcomes in rectal cancer - Siegel, Robert; Sibert, Nora Tabea; Breidenbach, Clara; Gani, Cihan; Neumann, Philipp Alexander; Benz, Stefan Rolf; Post, Stefan; Seufferlein, Thomas; Kolb, Vanessa; Behrend, Matthias; Blossey, Richard David; Bunse, Jörg; et al. (Colorectal disease, 2025)
Aim To prospectively evaluate the effect of preoperative radiotherapy followed by surgery versus surgery alone on patient-reported outcomes (PROs) 1 year after surgery. Method Prospective observational cohort study in 127 colorectal cancer centres. Patients with rectal cancer completed European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core (EORTC-QLQ-C30) and Colorectal module (-CR29) questionnaires (thus providing PROs) before initialization of treatment [baseline (T0)] and at 12 months after surgery [follow up (T1)]. The PRO data together with sociodemographic information were linked to clinical data. Relevant confounders were identified using directed acyclic graphs. The effect of preoperative radiotherapy on selected PROs 12 months after surgery was estimated using adjusted tobit regression models. Results Of 1635 patients with rectal cancer for whom both baseline and follow-up PROs were available, 565 (35%) received preoperative radiotherapy. Twelve months after surgery, patients with surgery alone reported better scores for global health status/Quality of Life, urinary incontinence, faecal incontinence (patients without stoma), dyspareunia (female patients) and impotence (male patients) than did patients receiving preoperative radiotherapy. The statistically significant effects ranged between 33.20 (p < 0.001, R2 = 0.19) for impotence and 39.01 (p = 0.001, R2 = 0.10) for dyspareunia. For global health status/QoL and urinary incontinence, no statistically significant effect could be found. Conclusion Radiotherapy in addition to surgery negatively affects selected PROs 1 year after surgery in patients with rectal cancer. Compared with surgery alone, patients report profoundly impaired bowel and sexual function after preoperative radiotherapy. However, global health status/QoL was not affected statistically significantly. These results are an important argument for limiting preoperative radiotherapy to patients with a high risk of recurrence of rectal cancer and may facilitate informed decision-making. Trial Registration German Clinical Trial Registry Number DRKS00008724 (https://drks.de/search/de/trial/DRKS00008724).
Erstmals veröffentlicht: 10. Juli 2025
Gesehen am 22.09.2025